Visfatin and VEGF levels are not increased in adolescent girls with polycystic ovary syndrome - Skrzyńska, Karolina; Zachurzok, Agnieszka; Pietrusik, Agnieszka; Jakubowska-Kowal, Karolina; Gawlik-Starzyk, Aneta (Frontiers in Endocrinology, 2024)
Introduction: PCOS is one of the most commonly occurring endocrinopathies among women and increasingly affects adolescent populations. The connection between PCOS and various endocrinological, psychological, and CVD is increasingly recognized. Some studies have shown elevated levels of visfatin and VEGF among patients with PCOS, which are markers of vascular endothelial dysfunction. In our study, we evaluated the concentration of these parameters, focusing solely on a group of adolescents with PCOS, to assess whether these early markers of CVD are present at an early stage of diagnosis.Material and methods: In total, 80 adolescent girls participated in the study. 47 adolescents diagnosed with PCOS were included in the study group (mean age 15.68±1.18 years, BMI 26.66±6.41 kg/m2), while the remaining 33 regularly menstruating individuals (mean age 15.79±1.22 years, BMI 25.44±7.24 kg/m2) were assigned to the control group. Each participant underwent imaging, biochemical, and hormonal tests. Additionally, markers of endothelial dysfunction: VEGF and visfatin, were measured in all adolescents.Results: Both VEGF and visfatin levels did not differ significantly between PCOS and control group (p=0.30 and p=0.15, respectively). In the group of adolescent girls with PCOS, visfatin was significantly correlated with HDL, FSH, cortisol, and testosterone levels >55 ng/dl. VEGF was significantly correlated with fasting glucose, glucose levels after OGTT, estradiol, and waist circumference >80 cm.Conclusion: It can be indirectly inferred that both visfatin and VEGF should not be used as early markers for cardiometabolic complications among adolescent patients with PCOS. On the other hand, low visfatin levels, through their negative correlation with HDL, may have a protective effect on cardiovascular complications, while low VEGF levels, through their positive 3 correlation with glucose levels, may have a protective influence on carbohydrate metabolism disorders.